Bystander Memory T Cells and IMiD/Checkpoint Therapy in Multiple Myeloma: A Dangerous Tango? - Sponaas, Anne Marit; Waage, Anders; Vandsemb, Esten N.; Misund, Kristine; Børset, Magne; Sundan, Anders; Slørdahl, Tobias Schmidt; Standal, Therese (Frontiers in Immunology, 2021)
In this review article we discuss the role of the memory T cells in multiple myeloma (MM) and how they may influence immune responses in patients that received immunomodulating drugs and check point therapy.